Islam in Russia: formations of tolerance - Galeeva, Diana (Routledge, 2025)
"Islam in Russia is a rare scholarly attempt to understand the tolerant nature of Islam in the modern Russian Federation since the state's official acceptance of Islam. The book explores the key factors that have contributed, over time, to the establishment of a co-existent form of Islam in modern multi-ethnic and multinational Russia. It also probes discussion of the role that Russian Muslim intellectuals have played in forming contemporary Russian Islam. It concludes that the co-existent form of Islam in Russia can be linked to three key factors: its historical emergence, the intellectual culture, and strong regional identities. This original and engaging examination of the development and identity of Islam in Russia is a useful resource for students and scholars of Global Islam, Islam in Europe, History of Russia, Islamic History, Islamic Thought, and Modern Religious History"--